Effects of total suspended solids concentration and composition on hyperspectral imaging under indoors and outdoors conditions - Ng, Joo Ching (Nanyang Technological University, 2021)
Singapore is an expanding coastal city. According to SingStat, the population of Singapore has reached 5.69 million as at the end of June 2020. With the large population density of 7,810 persons per square kilometres in 2020 (Department of Statistics, 2021), Singapore has been conducting land reclamation to increase land area for decades. Land reclamation activities tend to cause excessive sediments to be generated due to dredging, and along with that, destruction of original marine habitats follows. Water quality can deteriorate rapidly because of reclamation activities and uncurbed total suspended solids (TSS) levels can negatively impact water quality to a large extent. Thus, Singapore has implemented typical Environmental Management and Monitoring Programmes during land reclamation. The presence of TSS is one of the main reasons causing turbidity in marine water (Cai Rong, 2010). It is therefore of utmost importance to engage in remote sensing technology to gauge the TSS levels on a large spatial scale. In order to ensure marine waters are maintained at an acceptable level of TSS concentration, remote sensing using hyperspectral imaging camera can be used to monitor the TSS concentrations in real-time through detecting reflectance values. Significant wavelength band of 596.10nm that strongly correlates to TSS concentration is derived from the experiments and modelling. The highest R2 values analysed is 0.981 for indoors experiment and 0.890 for outdoors experiment, demonstrating a good fit by the simple linear regression model. This further confirms the strong correlation between TSS concentrations and compositions with reflectance.